2012
DOI: 10.1186/1471-2431-12-87
|View full text |Cite
|
Sign up to set email alerts
|

One third of middle ear effusions from children undergoing tympanostomy tube placement had multiple bacterial pathogens

Abstract: Background Because previous studies have indicated that otitis media may be a polymicrobial disease, we prospectively analyzed middle ear effusions of children undergoing tympanostomy tube placement with multiplex polymerase chain reaction for four otopathogens. Methods Middle ear effusions from 207 children undergoing routine tympanostomy tube placement were collected and were classified by the surgeon as acute otitis media (AOM) for purulent effusions and as otitis me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 25 publications
6
33
0
1
Order By: Relevance
“…In these treatment groups, M. catarrhalis was detected in 14, 11, 15, and 2 episodes, a This instance of PCR negativity of a sample containing H. influenzae was a consequence of the sequence of the forward primer. Some strains of H. influenzae are not detectable by the primer used in this study (16,24,32). The presence of H. influenzae in a high quantity was verified by sequencing the V3-to-V5 region of the bacterial 16S rRNA gene using generic primers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these treatment groups, M. catarrhalis was detected in 14, 11, 15, and 2 episodes, a This instance of PCR negativity of a sample containing H. influenzae was a consequence of the sequence of the forward primer. Some strains of H. influenzae are not detectable by the primer used in this study (16,24,32). The presence of H. influenzae in a high quantity was verified by sequencing the V3-to-V5 region of the bacterial 16S rRNA gene using generic primers.…”
Section: Resultsmentioning
confidence: 99%
“…To reinforce the finding, and to amend the design of the detection primer, we then retrieved available sequences of the 16S region of H. influenzae from GenBank, aligned them, removed the ambiguous sequences, and assessed the primer annealing site in the 557 remaining sequences. The H. influenzae-specific forward primer designed by Holder et al (16) and used here annealed with no mismatches to 401 of 557 retrieved sequences. Two other prevalent motifs were related to the forward primer annealing site: the first one differed by only two nucleotides in the 5=-proximal portion of the primer, so safe detection by the original primer may be reasonably expected; it was present in 53 of 557 retrieved sequences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR is a sensitive method for detecting bacterial DNA, requiring only small DNA fragments for amplification. It is thought that detection of bacterial DNA by PCR only represents the presence of live bacteria (Post et al, 1996;Hendolin et al, 2000;Holder et al, 2012). Studies involving PCR have shown that bacterial DNA exists in some MEE samples.…”
Section: Discussionmentioning
confidence: 99%
“…M. catarrhalis is a common cause of acute otitis media in children, along with nontypeable Haemophilus influenzae and Streptococcus pneumoniae (6). Studies using PCR to detect bacterial DNA in middle ear fluid reveal that M. catarrhalis plays an even larger role in otitis media than revealed by culture alone (15)(16)(17)(18). With the increasing widespread administration of pneumococcal conjugate vaccines globally, patterns of nasopharyngeal colonization in children and the distribution of pathogens causing otitis media are undergoing changes, with M. catarrhalis taking on a more prominent role (19).…”
mentioning
confidence: 99%